2002
DOI: 10.1007/s00335-001-3059-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative sequence analysis of the INS-IGF2-H19 gene cluster in pigs

Abstract: IGF2 is the major candidate gene for a paternally expressed Quantitative Trait Locus (QTL) in the pig primarily affecting muscle development. Here we report two sequence contigs together comprising almost 90 kb containing the INS-IGF2 and H19 genes. A comparative sequence analysis of the pig, human, and mouse genomic sequences was conducted to identify the exon/intron organization, all promoters, and other evolutionarily conserved elements. RT-PCR analysis showed that IGF2 transcripts originated from four diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
46
0
6

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 0 publications
9
46
0
6
Order By: Relevance
“…This may be due to the higher proportions of 5 m C and GC content, as well as more CpG islands in the pig than the other species (Amarger et al, 2002). Cloned pigs at 1 month of age had a higher concentration of 5 m C in their lung DNA than that of age-matched controls.…”
Section: Park Et Almentioning
confidence: 94%
“…This may be due to the higher proportions of 5 m C and GC content, as well as more CpG islands in the pig than the other species (Amarger et al, 2002). Cloned pigs at 1 month of age had a higher concentration of 5 m C in their lung DNA than that of age-matched controls.…”
Section: Park Et Almentioning
confidence: 94%
“…However, this is the first investigation of the imprinting status of the Rasgrf1 gene in swine. By first obtaining the partial exon 14 sequence, we found that, typical of imprinted genes (Amarger et al, 2002;Zhang et al, 2004), exon 14 of the porcine Rasgrf1 gene was highly GC-rich. Furthermore, a de novo polymorphism located in exon 14 of the porcine Rasgrf1 gene was discovered and was presented for the first time here (http://www.ncbi.nlm.nih.gov/ SNP/snp_ref.cgi?locusId=100157221).…”
Section: Discussionmentioning
confidence: 99%
“…Igf2 is a complex transcription unit that consists of seven non-coding exons and three coding exons for pre-pro Igf2. Exons 1, 4, 5, and 6 are preceded by distinct promoters P1, P2, P3, and P4 (Mineo et al 2000;Amarger et al 2002) which give rise to a family of mRNA transcripts having different leader exons with the same coding exons at the 3′ ends in human (Holthuizen et al 1990). Our results show that the expression of Igf2 differed by promoters.…”
Section: Discussionmentioning
confidence: 99%
“…H19 and insulin-like growth factor 2 (Igf2) are the most widely studied imprinted genes Amarger et al 2002;Shen et al 2012). Igf2 is expressed exclusively from the paternal allele, whereas the H19 gene is expressed from the maternal allele, and their imprinted gene expression is controlled by methylation of the H19 DMRs (Tremblay et al 1995).…”
Section: Introductionmentioning
confidence: 99%